2017
DOI: 10.5897/ijbc2016.1057
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of indigenous Maefur goat population in Tigray, Northern Ethiopia

Abstract: The study was conducted in Erob district eastern Tigray, Ethiopia to phenotypic characterize Maefur goat based on physical body feature and linear body measurements. Six hundred (297 male and 303 female) goats were randomly selected and grouped into four age groups of 0, 1, 2 and ≥3 PPI. General Linear Model (GLM) procedure of SPSS version 16.0 and descriptive statistical analysis were were used to summarize the collected data. Short ear size (12.3 cm for male and 11.8 cm for female), long and thick horn, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
2
2
2
Order By: Relevance
“…The findings from this study shows a positive correlation (r = 0.400; P < 0.05) between TP and BW. This differs from the findings of [37], who reported that change in protein levels had no effect on Body weight of Badali kids. Cholesterol is an energy source in all living organisms.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings from this study shows a positive correlation (r = 0.400; P < 0.05) between TP and BW. This differs from the findings of [37], who reported that change in protein levels had no effect on Body weight of Badali kids. Cholesterol is an energy source in all living organisms.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were reported by [36], from research with the indigenous Maefur goats in Ethiopia, where males were found to be heavier than female goats (42.8 ± 6.6 kg versus 37.2 ± 4.1 kg). [37] also had similar findings from research with the South African indigenous goat where 8 tooth male goats weighed 37.7 ± 7.17 kg whilst females of the same age weighed 31.4 ± 5.87 kg. There are challenges in communal farming set up, one of these is unavailability of weighing scales which assist in marketing live animals as well as selection for breeding purpose [38].…”
Section: Discussionsupporting
confidence: 73%
“…We noted that 80.28% of the population of northwestern Tunisia is horny. Several authors have also reported that the majority of animals are horny (Castanheira et al (2010) but the results of our study contradict other previous studies (Weldeyesus & Rohatash, 2017;Manallah, 2012) in different regions of Algeria. Among the 80.28% of horned individuals in our study population, 62.87% had horns with curved shapes.…”
Section: Qualitative Traitscontrasting
confidence: 90%
“…The economic/production traits (Table 2.) that influence the profitability of sheep farming in the study areas were collected from previous studies (Zelealem & Anal, 2014; Gizaw et al, 2016; Weldeyesus & Yayneshet, 2016; Welday et al, 2019).…”
Section: Methodsmentioning
confidence: 99%